2002
DOI: 10.1055/s-2002-36738
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Myasthenic Syndrome (CMS) in Three European Kinships due to a Novel Splice Mutation (IVS7 - 2 A/G) in the Epsilon Acetylcholine Receptor (AChR) Subunit Gene

Abstract: Mutations in the epsilon-acetylcholine receptor (AChR epsilon) subunit gene cause congenital myasthenic syndromes (CMS) with postsynaptic neural transmission defects. We present 3 male and 2 female patients from three unrelated Croatian, Hungarian, and Russian families with autosomal recessive CMS. All patients manifested with variable degrees of ophthalmoparesis and generalized, fatiguable muscle weakness since birth or early infancy. Electrophysiological studies showed a decremental response in all patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2005
2005
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Careful selection of patients with a few simple clinical features can lead to a percentage as high as 72.2% of patients with the mutation, which could be a useful tool for the first screening of CMS patients, including in different countries where other CHRNE mutations also have a founder effect. Main clinical data from patients with the CHRNE c.130dupG mutation + = present; -= absent; nd = no data or not tested; EO = early onset; IP = improvement with pyridostigmine; FS = fluctuating symptoms; IEM = imparied eye movement; PIE = partially impaired eye movement; SRI= impaired eye movement sparing rectus inferior muscles; PP = ptosis; LW = limb weakness; BS = bulbar symptoms; FI = facial involvement; NPC = no progressive course; Variants found associated with c.130dupG: c.803-2A>G (previously reported as pathogenic [11]); c.858_859dup (p.leu287ser fs*14, novel); c.422T>A (p.pro141.leu, previously reported as pathogenic [12]).…”
Section: Discussionmentioning
confidence: 99%
“…Careful selection of patients with a few simple clinical features can lead to a percentage as high as 72.2% of patients with the mutation, which could be a useful tool for the first screening of CMS patients, including in different countries where other CHRNE mutations also have a founder effect. Main clinical data from patients with the CHRNE c.130dupG mutation + = present; -= absent; nd = no data or not tested; EO = early onset; IP = improvement with pyridostigmine; FS = fluctuating symptoms; IEM = imparied eye movement; PIE = partially impaired eye movement; SRI= impaired eye movement sparing rectus inferior muscles; PP = ptosis; LW = limb weakness; BS = bulbar symptoms; FI = facial involvement; NPC = no progressive course; Variants found associated with c.130dupG: c.803-2A>G (previously reported as pathogenic [11]); c.858_859dup (p.leu287ser fs*14, novel); c.422T>A (p.pro141.leu, previously reported as pathogenic [12]).…”
Section: Discussionmentioning
confidence: 99%
“…Three other splicing mutations had been previously characterised. [2][3][4] To summarise, exons 5, 6, 8, 9, and 10 are skipped, and introns 7, 9, and 11 are retained. The three retained introns are all short (intron 7, 82 bp; intron 9, 83 bp; and intron 11, 109 bp), whereas four of five skipped exons flank medium to long introns on either or both sides (exon 5 is flanked by 129 and 306 bp introns; exon 6 by 306 and 334 bp introns; exon 8 by 82 and 1210 bp introns; and exon 9 by 1210 and 83 bp introns).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most common types of CMS is congenital AChR deficiency, which often results from mutations in CHRNE. A single CHRNE mutation, 1293insG, has been encountered in patients from America (12), eastern Europe (13), and North Africa (14), and it has been suggested that it may derive from a common founder.…”
mentioning
confidence: 99%